Cross‐sectional study exploring the association between stressors and burnout in junior doctors during the COVID‐19 pandemic in the United Kingdom. Issue 1 (13th January 2022) - Zhou, Anli Yue; Hann, Mark; Panagioti, Maria; Patel, Mumtaz; Agius, Raymond; Van Tongeren, Martie; Esmail, Aneez; Bower, Peter
Abstract: Objectives: This study aims to develop a comprehensive list of stressors relevant to junior doctors and will also report findings exploring the associations between burnout and stressors, which include work and non‐work–related stressors as well as pandemic‐related stressors. Methods: An anonymous online questionnaire was sent to 1000 randomly selected junior doctors in the North‐West of England. The questionnaire included 37 questions on general and pandemic‐specific stressors, and the Maslach Burnout Inventory Health Services Survey. The main outcomes of interest were junior doctor ratings of stressors and scores for burnout (emotional exhaustion [EE], depersonalisation [DP], and personal accomplishment [PA]). Stepwise regression analysis was undertaken to assess associations between stressors and burnout. Results: In total, 326 responses were collected (response rate = 33%). Of the top 10 stressors rated by junior doctors, 60% were related to the pandemic. Multiple stressors were found to be associated with the burnout dimensions. Fatigue ( β = .43), pandemic‐related workload increase ( β = .33), and feeling isolated ( β = .24) had the strongest associations with EE, whereas fatigue ( β = .21), uncertainty around COVID‐19 information ( β = .22) and doing unproductive tasks ( β = .17) had the strongest associations with DP. Working beyond normal scope due to COVID‐19 ( β = −.26), not confident in own ability ( β = −.24) and not feeling valued ( β = −.20) were found to have the strongest associations with PA. Conclusions: Junior doctors experience a combination of general stressors and additional stressors emerging from the pandemic which significantly impact burnout. Monitoring these stressors and targeting them as part of interventions could help mitigating burnout in junior doctors.